The relationship between social interaction abilities and physical education learning participation of childrens with special needs on locomotor movements in inclusive elementary schools - Julia Prastyaning Tyas; Donny Wira Yudha Kusuma; Hadi Hadi; Rohman Hidayat; Rifqi Festiawan (Universitas Riau, 2023)
(English)This study investigates the relationship between social interaction skills and physical education learning participation of children with special needs in locomotor movements in inclusive elementary schools. This research is a correlational study with a cross-sectional approach. The population in this study were all children with special needs in inclusive elementary schools in Rembang Regency. From 14 sub-districts in Rembang Regency, there are 205 inclusive elementary schools, with a total population of 1,333 students. The sampling technique used purposive sampling with inclusion and exclusion criteria so that 74 samples were obtained. The research instrument for social interaction skills and participation in physical education learning uses questionnaires and locomotor ability tests. From the research results it is known that 1) There is a positive relationship between Social Interaction Ability and Locomotor Movement; 2) There is a positive relationship between Physical Education Learning Participation of Students with Special Needs and Locomotor Movement; 3) There is a positive and significant relationship between Social Interaction Ability and Physical Education Learning Participation for Children with Special Needs and Locomotor Movement in Inclusive Elementary Schools in Rembang Regency using the multiple regression test. The conclusion is that there is a relationship between Social Interaction Ability and Locomotor Movement, Physical Education Learning Participation of Students with Special Needs and Locomotor Movement and Social Interaction Ability with Physical Education Learning Participation of students with special needs and Locomotor Movement in Inclusive Elementary Schools in Rembang Regency.(Indonesian)Penelitian ini bertujuan untuk menyelidiki hubungan antara kemampuan interaksi sosial dengan partisipasi pembelajaran pendidikan jasmani anak berkebutuhan khusus pada gerakan lokomotor di sekolah dasar inklusif. Penelitian ini merupakan penelitian korelasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh anak berkebutuhan khusus di sekolah dasar inklusi di Kabupaten Rembang. Dari 14 kecamatan di Kabupaten Rembang yang mencakup 205 Sekolah Dasar inklusi, dengan total populasi sebanyak 1.333 siswa. Teknik sampling menggunakan purposive sampling dengan kriteria inklusi dan ekslusi sehingga didapatkan 74 sampel. Instrumen penelitian keterampilan interaksi sosial dan partisipasi dalam pembelajaran pendidikan jasmani menggunakan angket dan tes kemampuan lokomotor. Dari hasil penelitian diketahui bahwa 1) terdapat hubungan positif antara Kemampuan Interaksi Sosial dengan Gerakan Lokomotor; 2) Terdapat hubungan positif antara Partisipasi Pembelajaran Pendidikan Jasmani Siswa Anak Berkebutuhan Khusus dengan Gerakan Lokomotor; 3) Terdapat hubungan yang positif dan signifikan antara Kemampuan Interaksi Sosial dengan Partisipasi Pembelajaran Pendidikan Jasmani siswa berkebutuhan khusus dan Gerak Lokomotor di Sekolah Dasar Inklusi Kabupaten Rembang menggunakan uji regresi berganda. Kesimpulannya adalah terdapat hubungan antara Kemampuan Interaksi Sosial dengan Gerakan Lokomotor, Partisipasi Pembelajaran Pendidikan Jasmani Siswa Anak Berkebutuhan Khusus dengan Gerakan Lokomotor dan Kemampuan Interaksi Sosial dengan Partisipasi Pembelajaran Pendidikan Jasmani siswa berkebutuhan khusus dan Gerak Lokomotor di Sekolah Dasar Inklusi Kabupaten Rembang.Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.